Circadian long call distribution in wild orangutans - Marina Davila Ross; Thomas Geissmann (Revue de Primatologie)
We present first data on circadian long call distribution of wild orangutans in Northwest Borneo. Data were collected during two months in Batang Ai National Park. A total of 151 male long calls were heard, exhibiting a bimodal distribution pattern with peaks at 05:00-06:00 hours and 18:00-19:00 hours. An earlier study found pronounced differences between the calling rates of Bornean orangutans, which showed an almost unimodal call distribution with its peak at mid-morning, and those of Sumatran orangutans, which showed a bimodal call distribution with a distinct calling peak at predawn and a more moderate peak near dusk (MacKinnon 1974). Our findings from Batang Ai resemble more closely the pattern reported for Sumatra than those reported for other Bornean localities and, therefore, contradict earlier reports suggesting a Sumatra-Borneo dichotomy in orangutan call distribution. In addition, orangutans in Batang Ai were heard to regularly emit long calls throughout the night. This behaviour is unusual for a diurnal species.